Eating habit, body image, and gender - is there any association? - A comparative study among medical students from southern India - R Aruna; Partheeban Muruganandam; S Niveatha (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: An increase in overweight and obesity among young adults are major health concerns which can influence their self-perception about body image. Body image has received a great deal of attention among young people. Body dissatisfaction is an extremely powerful construct that pervades our self-esteem, resulting in psychological impact and disordered eating. This study examines the association of body image dissatisfaction, disordered eating, and body mass index among medical students and its relationship with gender. MATERIALS AND METHODS: This cross-sectional study was conducted among 493 medical students. Body shape questionnaire (BSQ), Eating attitude test (EAT 26), and the Figure Rating Scale questionnaire were administered. Body mass index (BMI) and waist circumference (WC) were calculated using standard tools. RESULTS: Around half the participants (54%) had a concern with regard to their body shape with a female preponderance, and one-fourth of the study population (25%) had a higher risk for eating disorder. BSQ and EAT26 questionnaires had a significant positive correlation with BMI and WC. CONCLUSION: This study highlights a high prevalence of body image dissatisfaction among medical students who have direct positive correlation with BMI and WC. Health education programs addressing optimal weight and active lifestyle should be emphasized to reduce psychological burden in future.